2021
DOI: 10.3390/nursrep11010013
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions of Nurses and Nursing Students Regarding Family Involvement in the Care of Hospitalized Adult Patients

Abstract: Over the past few decades, there have been concerns regarding the humanization of healthcare and the involvement of family members in patients’ hospital care. The attitudes of hospitals toward welcoming families in this respect have improved. In Arab culture, the main core of society is considered to be the family, not the individual. The objective behind involving family in patient care is to meet patients’ support needs. Consequently, this involvement affects nurses and their attitudes toward the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Involving family members in the medical care of patients is often preferred by patients themselves, as family members can provide valuable information about the patient's functioning at home and support treatment compliance. However, Shibily et al [ 33 ] conducted a study on nurses and nursing students and found that nurses with more years of experience showed less support for family involvement in patient care. This negative correlation may be attributed to the time constraints experienced by senior nurses who are expected to multitask.…”
Section: Discussionmentioning
confidence: 99%
“…Involving family members in the medical care of patients is often preferred by patients themselves, as family members can provide valuable information about the patient's functioning at home and support treatment compliance. However, Shibily et al [ 33 ] conducted a study on nurses and nursing students and found that nurses with more years of experience showed less support for family involvement in patient care. This negative correlation may be attributed to the time constraints experienced by senior nurses who are expected to multitask.…”
Section: Discussionmentioning
confidence: 99%
“…This finding also confirmed that technical caring behaviour was more perceived among students than the psychosocial caring behaviour. Despite that, the presence of patient's families allows patients to know information about their status and improve patients' condition as well as improve communication between nurses and families and increase trust in treatments provided to patients (Shibily, 2021). Furthermore, a family was a source of bonding feelings which bridge patients and nurses in talking care of patients which in turn could increase nursing job satisfaction (Hagedom, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, the practice of health professionals has embodied the principles of PFCC and FCC to the point that nurses recognise that the presence of FRs at the bedside has a considerable influence on improving the condition of patients [ 4 ]. Hospital policies that allow the presence of FRs have been largely implemented showing their effectiveness among patients with dementia [ 5 ], cancer [ 6 ], cardiovascular diseases [ 7 ], and among frail elderlies [ 8 ].…”
Section: Introductionmentioning
confidence: 99%